Differences in gene regulation in a tephritid model of prezygotic reproductive isolation. Issue 5 (15th May 2019) - Raphael, K. A.; Sved, J. A.; Pearce, S.; Oakeshott, J. G.; Gilchrist, A. S.; Sherwin, W. B.; Frommer, M.
Abstract: The two tephritid fruit fly pests, Bactrocera tryoni and Bactrocera neohumeralis, are unusually well suited to the study of the genetics of reproductive isolating mechanisms. Sequence difference between the species is no greater than between a pair of conspecific Drosophila melanogaster populations. The two species exist in close sympatry, yet do not hybridize in the field, apparently kept separate by a strong premating isolation mechanism involving the time of day at which mating occurs. This spurred us to search for key genes for which time of day expression is regulated differently between the species. Using replicated, quantitative transcriptomes from head tissues of males of the two species, sampled in the day and night, we identified 141 transcripts whose abundance showed a significant interaction between species and time of day, indicating a difference in gene regulation. The brain transcripts showing this interaction were enriched for genes with a neurone function and 90% of these were more abundant at night than day in B. tryoni . Features of the expression patterns suggest that there may be a difference in the regulation of sleep–wake cycles between the species. In particular several genes, which in D. melanogaster are expressed in circadian pacemaker cells, are promising candidates to further explore the genetic differentiation involved in this prezygotic reproductive isolation mechanism.